Developing Augmented Reality Based Worksheets (LKPD) to Improve Learning Outcomes of Culinary Industry Kitchen Equipment Materials - Effelie Dewi Mayangsari; Nur Qudus (Mataram University, 2026)
This research was conducted to evaluate the development process, feasibility, practicality, and effectiveness of implementing an Augmented Reality (AR) based Student Worksheet (LKPD) focused on Culinary Industry Kitchen Equipment for 10th grade culinary students at SMK Widya Praja Ungaran. The study was initiated due to the limited visual representation of expensive laboratory equipment and a reliance on conventional, static worksheets that do not fully align with modern industry standards. Utilizing a Research and Development (R&D) approach with the 4D model (Define, Design, Develop, Disseminate), data were gathered via expert evaluation sheets, student feedback questionnaires, and learning achievement assessments measured through pre-tests and post-tests from 69 participants divided into experimental and control classes. The findings revealed that the development successfully combined printed worksheet with an Android-compatible AR app created via Unity and Vuforia SDK. Content and media experts rated the learning media as highly feasible, scoring 94.58% and 90.00% respectively. Moreover, a student questionnaire score of 88.89% confirmed its high practicality. The effectiveness analysis through an Independent Samples T-Test showed a significance value of 0.000 (Sig. < 0.05), proving a substantial gap in performance between both groups. The experimental group achieved a high average Normalized Gain (N-Gain) score of 0.72, surpassing the control group's score of 0.23. In conclusion, the AR integrated LKPD is validated as a viable, practical, and effective educational medium for advancing students' cognitive performance in industrial kitchen equipment topic.